Subacute Toxicity Evaluation of Methanolic Extract of Syzygium polyanthum in Rats - Nor Hazliana Harun; Nor Atiqah Rasdi; Rabeta Mohd Salleh; Sabreena Safuan; Wan Amir Nizam Wan Ahmad; Wan Ezumi Mohd Fuad (Tropical Life Sciences Research, 2021)
Syzygium polyanthum (Wight) Walp. var. polyanthum (serai kayu) leaves is a popular herb and widely used in traditional medicine. Despite the ethnomedicinal benefits, very limited studies have researched on the toxicity of this plant. The aim of the present study was to investigate the potential effects of methanolic extract of Syzygium polyanthum (MESP) leaves via 28-day repeated oral dosing in Sprague Dawley rats. MESP leaves was administered at doses of 0 (control), 400, 1000 or 2000 mg/kg to an equal number of male and female rats (n = 10/group). Results obtained indicated that MESP did not affect the general conditions (body weight, feed intake and oestrous cycle) and apparent behavioural changes of the rats. Biochemical parameters revealed a slight significant variation in the aspartate aminotransferase (AST) level between the male rats treated with the lowest and highest doses of MESP, but these findings were both statistically insignificant when compared to the control group. The liver of the males (dose 1000 and 2000 mg/kg/day) also exhibited histoarchitectural defects on the hepatocytes and cytoplasm when compared to those of the control group. In contrast, female rats did not encounter any significant findings in all parameters tested. In conclusion, this study suggests that the MESP leaves might exhibit sex-based variation effects and thus, the use of this extract particularly at higher doses should be thoroughly considered.